PyCorrFit—generic data evaluation for fluorescence correlation spectroscopy - Müller, Paul; Schwille, Petra; Weidemann, Thomas (Bioinformatics (Oxford, England), 2014)
We present a graphical user interface (PyCorrFit) for the fitting of theoretical model functions to experimental data obtained by fluorescence correlation spectroscopy (FCS). The program supports many data file formats and features a set of tools specialized in FCS data evaluation. Availability and implementation: The Python source code is freely available for download from the PyCorrFit web page at http://pycorrfit.craban.de. We offer binaries for Ubuntu Linux, Mac OS X and Microsoft Windows. Contact:  paul.mueller@biotec.tu-dresden.de and weidemann@biochem.mpg.de